2017
DOI: 10.4274/tjh.2016.0427
|View full text |Cite
|
Sign up to set email alerts
|

Genotype – Phenotype Correlations of β-Thalassemia Mutations in Azerbaijani population

Abstract: β-Thalassemia is the most common inherited disorder in Azerbaijan. The aim of our study was to reveal genotype-to-phenotype correlations of the most common β-thalassemia mutations in an Azerbaijani population. Patients with codon 8 (-AA), IVS-I-6 (T>C), and IVS-II-1 (G>A) mutations, which are reportedly the most common β-globin gene mutations among the local population, were tested for hematologic parameters. Fifty-five previously tested patients with known genotypes were included in the study. Hematologic ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…It was also found that the in the (LCR - HS2) β- had an effect on the hemoglobin F ratio, as it increases number of patients, with 99% confidence. This finding was consistent with Asadov et al ( Asadov et al, 2017 ).…”
Section: Discussionsupporting
confidence: 94%
“…It was also found that the in the (LCR - HS2) β- had an effect on the hemoglobin F ratio, as it increases number of patients, with 99% confidence. This finding was consistent with Asadov et al ( Asadov et al, 2017 ).…”
Section: Discussionsupporting
confidence: 94%
“…Beta (zero)-thalassemia apparently has a more severe clinical presentation, causing thalassemia major in homozygous and compound heterozygous states, whereas beta(+)-thalassemia are observed as milder cases of thalassemia intermedia. 11 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, point mutations occurring on the α-globin genes are associated with more severe α-thalassemia phenotypes compared to deletional mutations. Thus, determination of the genotype is essential for prediction of the clinical severity of thalassemia [42][43][44].…”
Section: Molecular Diagnosismentioning
confidence: 99%